SUPLEMENTASI JAHE PADA TERAPI RHINITIS ALERGI - NAYOAN, CHRISTIN; nayoan, christin rony; Situmorang, Corymela; Towidjojo, Vera Diana (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran, 2025)
Allergic rhinitis (AR) is an inflammatory reaction in the nasal mucosa mediated by IgE2. The prevalence of allergic rhinitis in adults ranges from 17% - 28.5%. Indonesia is a tropical country that has thousands of types of plants used as herbal medicines. One of the plants that is often used as a traditional medicine is ginger. Red ginger rhizome contains gingerol which has antioxidant, antibacterial, anti-inflammatory, anticarcinogenic, antimutagenic, and antitumor activities. The purpose of this paper is to determine the effect of ginger supplementation on Allergic Rhinitis therapy.